Formulation of Slice Jam from Star Gooseberry (Phyllanthus acidus): Effect of Sucrose and Carrageenan Concentration on Physicochemical and Sensory Characteristics - Shellien Arik Subekti; Rosida Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Star gooseberry (Phyllanthus acidus) is a tropical fruit rich in vitamin C, phenolic compounds, and pectin, but its utilization remains limited due to high acidity and short shelf life. This study aimed to analyze the effects of sucrose and kappa-carrageenan concentrations on the physicochemical and sensory characteristics of star gooseberry slice jam and to determine the best formulation. A two-factor Completely Randomized Design was employed, comprising sucrose (55%, 60%, 65%) and kappa-carrageenan (2%, 4%, 6%) with two replications. Sensory evaluation was conducted by 30 semi-trained panelists. Results showed that the interaction between sucrose and carrageenan significantly affected ($p \le 0.05$) antioxidant activity, texture profile (hardness, cohesiveness, gumminess), and sensory scores for taste, color, and texture. Based on the De Garmo effectiveness index, the optimal formulation was 65% sucrose and 4% carrageenan (effectiveness value 1.317). This treatment yielded a slice jam with 7.41% moisture, pH 3.55, 77.70% total soluble solids, 73.54% total sugar, 76.37% antioxidant activity, 18.83 mg/100 g vitamin C, 107.65 N hardness, 0.432 cohesiveness, ?0.00111 J adhesiveness, and 46.51 N gumminess.. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and Production- loss.SDG 3: Good Health and Well-being SDG 2 : Zero HungerSDG 8 : Decent Work and Economic Growth-